1981
DOI: 10.1029/gl008i003p00277
|View full text |Cite
|
Sign up to set email alerts
|

UHF scintillation activity over polar latitudes

Abstract: Polar cap ionospheric irregularities have been monitored for several years from Thule Air Base, Greenland using 250 MHz satellite beacon scintillation measurements. The seasonal pattern of the polar cap irregularities shows very high intensity levels during the winter and lower levels during the summer (sunlit) months. This behavior is similar to in‐situ polar cap electric field measurements which show larger fluctuations in the winter than in the summer, an effect which may be related to E layer conductivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 8 publications
4
35
0
Order By: Relevance
“…Recent work in [7] over the period of solar minimum (2007)(2008) at two polar region stations at Ny-Ålesund, Svalbard (78.9°N, 11.9°E) and Larsemann Hill, East Antarctic (69.4°S, 76.4°E) concluded that phase scintillation and irregularities observed from GISTM receivers mainly takes place in October, November and December at NyÅlesund, and in May and June at Larsemann Hill. This is in agreement with the finding in [8].…”
Section: Previous Worksupporting
confidence: 83%
“…Recent work in [7] over the period of solar minimum (2007)(2008) at two polar region stations at Ny-Ålesund, Svalbard (78.9°N, 11.9°E) and Larsemann Hill, East Antarctic (69.4°S, 76.4°E) concluded that phase scintillation and irregularities observed from GISTM receivers mainly takes place in October, November and December at NyÅlesund, and in May and June at Larsemann Hill. This is in agreement with the finding in [8].…”
Section: Previous Worksupporting
confidence: 83%
“…The additional geo-stationary scintillation data from Tromso and Thule presented in Section 3 provide much new information when considered in tandem with earlier published work from Thule (Aarons et al, 1981), Goose Bay (Basu et al, 1988), and Narssarsuaq (Basu, 1975;Basu and Aarons, 1980). If we start with the Thule data which refers to the central polar cap, then we find that the UT seasonal and solar cycle dependence of scintillations are generally consistent with transport of plasma from sub-cusp latitudes taken in conjunction with the shorting effect of a sunlit E-region in the summer on F-region irregularities.…”
Section: Discussionsupporting
confidence: 52%
“…However, uhf scintillation measurements, a measure of km-scale irregularities, do not show a strong dependence on the level of geomagnetic activity. Scintillation occurrence measured from Thule, Greenland (860 CGL), was shown by Aarons et al 8 to be essentially independent of K p. Thus, during disturbed geomagnetic periods, when structured particle precipitation into the polar cap does not directly produce the observed irregularities, transport of plasma and irregularities from other production regions must be considered.…”
mentioning
confidence: 99%